Pt catalysts supported on polybenzimidazole nanofibrous mats: Tailored electrospinning leading to different morphology and platinum dispersion. Application to VOC oxidation - Soukup, Karel; Balabánová, Jana; Fernandez, Emma; Kupčík, Jaroslav; Topka, Pavel (Catalysis today, 2026)
Platinum nanoparticles were supported on polybenzimidazole nanofibrous mats prepared by electrospinning. We have shown that electrospinning from solution, colloid, or suspension leads to different morphologies of the support. Consequently, catalysts with various Pt dispersions were obtained after the impregnation of the support with platinum acetylacetonate. In the gas-phase oxidation of model volatile organic compounds (toluene, acetone, and ethanol), the catalytic activity sharply increased when the mean Pt particle size changed from 9 to 11 nm. During catalytic tests, sintering of Pt nanoparticles was observed, which contributed to an increased catalytic activity of the aged catalysts. The sintering was ascribed to the creation of hotspots at Pt active sites. The main advantage of using electrospun polybenzimidazole as a support material is its high porosity (up to 80 %). Thus, the effect of internal diffusion can be suppressed and the Pt active sites are easily accessible to the reactants. The obtained results highlight the critical role of nanofibrous catalyst morphology in tailoring metal dispersion and catalytic performance, offering a versatile support for the design of high-performance VOC oxidation catalysts. [Display omitted] •Polybenzimidazole mats prepared via solution, suspension, and colloid electrospinning.•Mat morphologies influenced Pt particle size after impregnation with Pt(acac)2.•Activity in VOC oxidation increased with Pt particle size increase from 9 to 11 nm.•Pt agglomerates formed after repeated light-off tests enhanced activity.•High porosity (∼80 %) of mats minimized internal diffusion.